The oncological outcomes of isolated limb perfusion and neo-adjuvant radiotherapy in soft tissue sarcoma patients - A nationwide multicenter study. Issue 2 (February 2023) - van Praag, V.M.; Fiocco, M.; Bleckman, R.F.; van Houdt, W.J.; Haas, R.L.M.; Verhoef, C.; Grunhagen, D.J.; van Ginkel, R.J.; Bonenkamp, J.J.; van de Sande, M.A.J.
Abstract: Introduction: Patients with locally extensive high-grade extremity soft tissue sarcomas (eSTS) are often presented in multidisciplinary teams to decide between ablative surgery (amputation) or limb-salvage surgery supplemented with either neo-adjuvant radiotherapy (RT) or induction isolated limb perfusion (ILP). In The Netherlands, ILP typically aims to reduce the size of tumors that would otherwise be considered irresectable, whereas neo-adjuvant RT aims mainly at improving local control and reducing morbidity of required marginal margins. This study presents a 15-year nationwide cohort to describe the oncological outcomes of both pre-operative treatment strategies. Methods: All consecutive patients with locally extensive primary high-grade eSTS surgically treated between 2000 and 2015 at five tertiary sarcoma centers that received neo-adjuvant ILP or RT were included. 169 patients met the inclusion criteria (89 ILP, 80 RT). Median follow-up was 7.3 years. Results: Limb salvage was achieved in 84% of cases in the ILP group (80% for patients with amputation indication) and 96% of cases in the RT group. 5-Year overall survival was 47% in the ILP group, 69% in the RT group. 5-Year local recurrence rate was 14% in the ILP group, 10% in the RT group. Distant metastasis rate was 55% in the ILP group, 36% in the RT group. Conclusion: We find oncological outcomes and limb salvage rates in line with existing literature for both treatment modalities. Whether the tumor was locally advanced with an indication for induction therapy to prevent amputation or morbid surgery appeared to be the main determinant in choosing between neo-adjuvant ILP or RT.